Cuban Americans and the Miami media - Lohmeier, Christine, 1978- (McFarland & Company, Inc., Publishers, 2014)
"This book makes a contribution to debates on diasporic identities and transnational communication. This is an analysis of the Cuban-American community and their relationship to Miami-based English- and Spanish-language media. Based on ethnographic data, the author demonstrates how different media have been used, produced and influenced by segments of the Cuban-American community in Miami"--